2001
DOI: 10.1258/0023677011911958
|View full text |Cite
|
Sign up to set email alerts
|

Middle-latency auditory evoked potentials during induction of thiopentone anaesthesia in pigs

Abstract: A method is described for measuring middle-latency auditory evoked potentials (MLAEP) in consciously awake, non-sedated pigs during the induction of thiopentone anaesthesia (0.6 ml/kg, 2.5% thiopentone solution). It was done by using autoregressive modelling with an exogenous input (ARX). The ability to perceive pain during the induction was compared with (1) the changes in latencies and amplitudes of the MLAEP, (2) the change in a depth of anaesthesia index based on the ARX-model and (3) the change in the 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…This delay in the onset of unconsciousness in the results of Raj (1999) and Martoft et al (2001) was also found by Rodriguez et al (2008) who monitored the brain activity using AEP and concluded that the onset of unconsciousness occurred after 60 s of exposure to 90 CO 2 . Raj (1999) and Martoft et al (2001) obtained different results, but in both studies pigs were hung in a hammock and rapidly immersed in a box that contained the modified atmosphere. However, in our experiment, as well as in that by Rodriguez et al (2008), the methodology of the gas exposure simulated commercial conditions, where pigs are immersed gradually to the required concentration in the base of a pit.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…This delay in the onset of unconsciousness in the results of Raj (1999) and Martoft et al (2001) was also found by Rodriguez et al (2008) who monitored the brain activity using AEP and concluded that the onset of unconsciousness occurred after 60 s of exposure to 90 CO 2 . Raj (1999) and Martoft et al (2001) obtained different results, but in both studies pigs were hung in a hammock and rapidly immersed in a box that contained the modified atmosphere. However, in our experiment, as well as in that by Rodriguez et al (2008), the methodology of the gas exposure simulated commercial conditions, where pigs are immersed gradually to the required concentration in the base of a pit.…”
Section: Discussionsupporting
confidence: 67%
“…Statistical analysis Data were analysed with the Statistical Analysis System (SAS 9.2, SAS Institute Inc., Cary, NC, 1999-2001. Latency measures (such as time to the first gasping, loss of balance, vocalization, onset and duration of muscular excitation, the time to reappear pain sensitivity, rhythmic breathing and corneal reflex), IoC and ESR data were analysed using a mixed model ANOVA (PROC MIXED) with a covariance structure of compounds symmetric with 'gas mixture' and 'time of exposure' as fixed effects.…”
Section: Facilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The trachea was orally intubated (4.0 mm) and anesthesia was maintained with continuous infusions of fentanyl (30 mg Á kg À1 Á hr À1 ), midazolam (0.4 mg Á kg À1 Á hr À1 ), and propofol (3 mg Á kg À1 Á hr À1 ). The depth of anesthesia was monitored by auditory evoked potential (A-Line AEP monitor, Danmeter, Odense, Denmark) as described by Martoft,7 and the AAI-index kept below 30. The piglet was ventilated with volumecontrolled mechanical ventilation (Servo 900 C, Solna, Sweden) with FiO 2 0.7, tidal volume 8 ml Á kg À1 , PEEP 5 cmH 2 O, and the respiratory rate was adjusted to keep PaCO 2 between 5.5-6.5 kPa.…”
Section: Methodsmentioning
confidence: 99%